Shortening of the Bleeding Time in Rabbits by Hydrocortisone Caused by Inhibition of Prostacyclin Generation by the Vessel Wall - Blajchman, M. A. (1979)
The effect of hydrocortisone on thrombocytopenic bleeding has been studied in rabbits using a jugular vein bleeding-time technique and a microvascular bleeding-time technique. An inverse relationship was found between the bleeding time and platelet count with both techniques in rabbits made thrombocytopenic by either X-irradiation or injection of heterologous platelet antiserum. Hydrocortisone shortened both bleeding times in thrombocytopenic animals when given in single large doses intravenously (25-100 mg/kg), in daily doses (6 mg/kg) intramuscularly, and shortened the jugular bleeding time when applied to the outside of the jugular vein or instilled intraluminally into the vein. This effect was also noted in normal animals. The effect on thrombocytopenic bleeding was dose related. When given daily, the effect was greater when hydrocortisone was given for 10 d than for 5 d. Both indomethacin and tranylcypromine also reduced the jugular vein bleeding time when instilled intraluminally into the jugular vein, whereas exogenously provided arachidonic acid reversed the effect of hydrocortisone but did not reverse the effect of indomethacin or tranylcypromine. Exogenously provided linoleic acid did not have any effect. Perfusion of the vessel segment with prostacyclin (PGI(2)) reversed the effect of intraluminally administered hydrocortisone, indomethacin, and tranylcypromine. Similarly, hydrocortisone, indomethacin, and tranylcypromine all reduced the rate of loss of fluid from a standard wound in isolated vessels emptied of blood and perfused with saline under constant pressure. PGI(2) reversed the action of these three agents, however, arachidonic acid reversed only the effect of hydrocortisone and did not reverse the effect of indomethacin and tranylcypromine. The generation of PGI(2)-like material and 6-keto-prostaglandinF(1) α from jugular vein strips was prevented by prior exposure of the animals or vessel wall to hydrocortisone. These results are compatible with the hypothesis that the vessel wall releases smooth muscle-relaxing prostaglandins when injured and that inhibition of prostaglandin formation by hydrocortisone enhances hemostasis by allowing vasoconstriction to be maintained.